Absence of association between Guillain-Barré syndrome hospitalizations and HPV-vaccine - Geneviève Deceuninck; Chantal Sauvageau; Vladimir Gilca; Nicole Boulianne; Gaston De Serres (Expert Review of Vaccines, 2018)
Background: In 2008, a school-based human papilloma virus (HPV) vaccination program was implemented in the province of Québec. Grade 4 girls (9–10 years old) are routinely vaccinated and grade 9 to 12 girls (14–17 years old) were eligible for the catch-up vaccination. Vaccine coverage of the targeted cohorts was estimated at 76–81%. To assess if HPV vaccination is associated with an increase in GBS hospitalisation, we compared the hospitalization rates of GBS in HPV vaccination targeted and non-targeted groups. Methods: Hospital discharge records with a GBS code as the main diagnosis during the 1999–2014 period were retrieved. Incidence rates according to program eligibility were computed and adjusted relative risk in the targeted groups was estimated by Poisson regression. Results: The overall incidence rate in the 7 to 17 year-olds was 0.73/100,000 p-y. There was no increase in GBS incidence in HPV vaccination targeted groups (adjusted IRR = 0.81, 95%CI: 0.29–2.26). Conclusion: No signal of increase GBS hospitalisation incidence in the HPV-vaccine targeted group was detected in the hospitalisation database.